A NEW ERA OF ECONOMICS: DIVING INTO THE IMPACT OF DIGITAL TRANSFORMATION ON GLOBAL MARKET STRUCTURES - Loso Judijanto; Sulfianty; Mohd Syahrin (CV. Adiba Aisha Amira, 2024)
Digital transformation has given birth to a new era of economics that is changing the structure and dynamics of the global market. Advanced technologies such as the Internet of Things (IoT), artificial intelligence (AI), and data analytics are facilitating innovation and operational efficiency across various industry sectors. These changes not only affect the way companies operate but also shift consumer expectations and redefine traditional business models. This paper explores the impact of digital transformation on the global market structure and illustrates the adaptations required by companies to remain competitive and relevant.